2014
DOI: 10.1021/es5034266
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Uptake of an Isoprene-Derived Epoxydiol to Submicron Aerosol Particles

Abstract: The reactive uptake of isoprene-derived epoxydiols (IEPOX) is thought to be a significant source of atmospheric secondary organic aerosol (SOA). However, the IEPOX reaction probability (γIEPOX) and its dependence upon particle composition remain poorly constrained. We report measurements of γIEPOX for trans-β-IEPOX, the predominant IEPOX isomer, on submicron particles as a function of composition, acidity, and relative humidity (RH). Particle acidity had the strongest effect. γIEPOX is more than 500 times grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
402
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(426 citation statements)
references
References 88 publications
19
402
5
Order By: Relevance
“…More likely, the low observed mixing ratios of IEPOX at SOAS may be due to error in its production rate or because heterogeneous loss reactions, such as conversion to organic aerosols in anthropogenically impacted particle liquid water (64), were not accounted for in the model. IEPOX uptake clearly involves hydronium-catalyzed ring opening in aerosol liquid water (62,65,66). However, field results suggest that more factors than acid catalysis govern the chemistry (67).…”
Section: Resultsmentioning
confidence: 99%
“…More likely, the low observed mixing ratios of IEPOX at SOAS may be due to error in its production rate or because heterogeneous loss reactions, such as conversion to organic aerosols in anthropogenically impacted particle liquid water (64), were not accounted for in the model. IEPOX uptake clearly involves hydronium-catalyzed ring opening in aerosol liquid water (62,65,66). However, field results suggest that more factors than acid catalysis govern the chemistry (67).…”
Section: Resultsmentioning
confidence: 99%
“…Ozone exposure studies have shown that comparable dose and effect measurements for IL-8 and COX-2 can be found between in vivo and in vitro exposures, which adds promise to extrapolating effects seen in vitro to effects in vivo (Hatch et al, 2014). In vivo effects associated with isoprene SOA exposure in vitro cannot be inferred as it is a different system from ozone, so further in vitro studies exploring the health implication of the elevation of IL-8 and COX-2 due specifically to isoprene SOA exposure are necessary and may in turn justify further extension to in vivo work.…”
Section: Biological Implicationsmentioning
confidence: 91%
“…to particle acidity, which enhances isoprene SOA formation through acid-catalyzed reactive uptake and multiphase chemistry of IEPOX and MAE (Surratt et al, 2007Gaston et al, 2014;Riedel et al, 2015), while NO x determines whether the oxidation pathway leading to IEPOX or MAE/HMML predominates (Lin et al, 2013b;. Isoprene SOA comprises a large portion of global atmospheric fine particles (PM 2.5 , aerosol with aerodynamic diameters ≤ 2.5 µm) (Carlton et al, 2009;Henze et al, 2008), but few studies have focused on its health implications .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A large fraction of the total increase in SOA IEPOX/MPAN (red line) is due to increases in 2-MG production (grey line) even though 2-methyltetrols dominate the concentration of total SOA IEPOX/MPAN in most of the domain. If the Henry's law coefficient for IEPOX is much higher than used here (for example, 1.7 × 10 8 ; Gaston et al, 2014), then aqueous processing of IEPOX would lead to even higher methyltetrol concentrations than predicted here.…”
Section: Impact Of Cloud Soa Formation Pathway From Biogenic Epoxidesmentioning
confidence: 65%